Military Experience and Individual Entrepreneurship—Imprinting Theory Perspective: Empirical Evidence From China. (March 2023) - Wang, Haojun; Wang, Ying; Lyu, Bei; Yang, Yanchao; Huang, Honghong
Military experience, as a special early experience exerts a very profound impact on individual decision making. This paper investigates the impact of military experience on male labor force entrepreneurial choices and its underlying mechanisms, using the 2014 to 2016 China Labor-force Dynamics Survey data. It is found that military experience significantly reduces the probability of individual entrepreneurship. The analysis of the influence mechanism shows that military experience inhibits survival entrepreneurship mainly by increasing employment opportunities in state-owned units, increasing the probability of becoming a member of the Communist Party of China(CPC), and accumulating human capital. This paper also finds that the inhibitory effect of military experience on individual entrepreneurship varies across household registration groups and is more significant for laborers with non-agricultural household. This paper not only reveals the impact of the military experience on individual entrepreneurship choices, but also provides empirical evidence for the development of innovation and entrepreneurship policies in emerging economies.